Evaluation of prolactin and insulin resistance in women with polycystic ovarian syndrome - Kundu, Dipankar; Ghosh, Enakshi; Mandal, Asit Baran; Basu, Satyaki (International Journal of Medical Research and Review, 2019)
Background: Polycystic ovarian syndrome has been one of a major public health problem in India that leads to medical consequences. It causes multifactorial in etiology such as menstrual dysfunction, hyperandrogenism, hirsutism, insulin resistance, dyslipidemia and obesity which increased risk of diabetes mellitus and cardiovascular disease. Prolactin has been reported as a potent lipogenic and diabetogenic factor, that affecting energy balance and fuel metabolism. The present study was designed to assess serum prolactin and insulin resistance in PCOS women and to compare them with healthy women as controls. Material and Methods: A comparative study including 50 women diagnosed as PCOS and 50 age and BMI matched healthy women as controls was conducted. The age group for the study was 18-35 years. Body Mass Index was calculated as a physical parameter. Fasting blood samples were drawn to assess serum prolactin, serum insulin, HbA1c and fasting blood sugar. Insulin resistance was calculated by homeostasis model assessment. Results: A significant increase in fasting serum insulin (p<0.001) and HOMA – IR (p<0.001) were found in patients with PCOS in comparison with controls. Mean BMI, prolactin, HbA1c and FBS were found elevated in the PCOS women but they were not statistically significant. No significant correlations were found between BMI, serum prolactin and serum insulin. Conclusions: The current study provides further evidence that significantly higher fasting insulin and HOMA in PCOS group indicates presence of IR. IR in PCOS group may have a potential role in the prediction of dysglycemic disease in women with PCOS. This study could not find any significant correlation between serum prolactin, serum insulin and BMI.